“GRIEF AND RESILIENCE LIVE TOGETHER”: AN ASSESSMENT OF ARTHUR MILLER’S DEATH OF A SALESMAN - Philomena Ama Okyeso Yeboah; Paul Otoo; James Gyimah Manu; Philip Kwame Freitas (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2022)
The present study was carried out to assess Mrs. Obama’s assertion, “grief and resilience live together”, in Miller’s tragedy, Death of a Salesman, from the theoretical perspectives of Marxism and Psychoanalysis. Using a qualitative content analysis, the paper finds that even though the protagonist meets his tragic end through his sufferings and disillusion, he displays unparalleled courage, resilience and optimism, as a common man, in a battle with the capitalist society. The paper affirms the afore-said statement and limns the defects of capitalism and its consequences on its victims – more so their psyche and mental state. With this paper, the researchers seek to expose the ills of capitalism and its devastating effects on the working-class members of the society.